Gout With Associated Cutaneous AA Amyloidosis: A Case Report and Review of the Literature - Orchard, G. E. (British Journal of Biomedical Science, 2023)
Gout with associated AA amyloidosis is an unusual finding. This form of amyloid is associated with chronic inflammatory changes often associated with amyloid deposits in the urine, as well as tissue involvement, and organ enlargement in some cases. The large majority of cases in the literature to date refer to gout with AA amyloid within the kidney. However, this is not exclusive, with reports in the liver, gastrointestinal tract, adrenal glands rectum, skin, and subcutaneous fat. The pathophysiological association between these two disease processes is open to debate. The employment of specific anti-inflammatory treatments is believed to have an impact on reducing the incidence of AA amyloidosis in some gout cases–notably the use of colchicine in cases of clinically defined gout attacks. However, this is by no means a universal finding. Here we report on a cutaneous case of gout with AA amyloidosis in a 73-year-old man Included in this case study is a review of the other 16 cases reported within the literature in an attempt to clarify the associated pathophysiological process between these two diseases and the anti-inflammatory treatment regimens employed which may impact the occurrence of AA amyloidosis.